Crystallization behavior in miscible blends of poly(ε‐caprolactone) and poly(hexylene adipate) with similar thermal properties studied by time‐resolved Fourier transform infrared spectroscopy. Issue 1 (13th December 2018) - Rohindra, David; Lata, Roselyn; Kuboyama, Keiichi; Ougizawa, Toshiaki
Abstract: Melt crystallization behavior in miscible blends of poly(e‐caprolactone) and poly(hexylene adipate) was investigated by Differential Scanning Calorimetry, Polarized Optical Microscopy, Wide Angle X‐Ray Diffraction and time resolved Fourier Transform Infrared Spectroscopy. Both polymers were highly crystalline, had similar thermal properties and exhibited negative birefringence. Fractional crystallization of PCL was observed in blends with <40 wt% PCL. Crystallization kinetics of the polyesters was investigated by monitoring the absorbance intensities of the bands at 841 and 911 cm −1 for PCL and PhAd respectively. Even though PCL exhibited a slow crystallization rate than PhAd at 47°C, simultaneous onsets of crystallization were found in all the blends. In blends with high PCL, the relative crystallinity vales for both the polyesters were found to be coincidental while for blends with low PCL content the induction time of PCL shortened due to PhAd playing the role of nucleation agent. WAXD ruled out co‐crystallization. Abstract : Poly(ε‐caprolactone) and poly(hexylene adipate) have similar thermal properties. The crystallization behavior studied by time resolved infrared spectroscopy at 47°C revealed that blends with high PCL exhibited simultaneous crystallization while blends with low PCL showed fractional crystallization. The crystallization kinetics of the two polymers were completely opposite. WAXD ruled out co‐crystallization. PhAd acted as the nucleation agent for PCL in the blends. FTIR spectroscopy is a useful technique to track crystallization in this blend system.